2023
DOI: 10.1021/acs.langmuir.3c00030
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Sensing Performances of MoTe2 Monolayers Doped with Pd, Ni, and Pt for SO2 and NH3: A DFT Investigation

Abstract: Density functional theory (DFT) calculation was used to study the adsorption and sensing performances of a transition metal atom (TMA) doped MoTe 2 monolayer for two industrial toxic and harmful gases, SO 2 and NH 3 , in this study. The adsorption structure, molecular orbital, density of state, charge transfer, and energy band structure were applied to investigate the interaction between the gas and MoTe 2 monolayer substrate. The conductivity of the MoTe 2 monolayer film doped with TMA (Ni, Pt, Pd) is signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 61 publications
1
11
0
1
Order By: Relevance
“…In this article, several common industrial waste gases have been selected. Their optimized structures and geometric parameters are shown in Figure , which is consistent with the results of previous studies. Figure a shows the optimized pure WSe 2 single-layer structure. After measurement, the average bond length of W–Se is 2.55 Å, and the band gap of pure WSe 2 is calculated to be 1.50 eV, similar to the previous studies. …”
Section: Resultssupporting
confidence: 87%
“…In this article, several common industrial waste gases have been selected. Their optimized structures and geometric parameters are shown in Figure , which is consistent with the results of previous studies. Figure a shows the optimized pure WSe 2 single-layer structure. After measurement, the average bond length of W–Se is 2.55 Å, and the band gap of pure WSe 2 is calculated to be 1.50 eV, similar to the previous studies. …”
Section: Resultssupporting
confidence: 87%
“…This includes improvements like higher adsorption energy, increased charge transfer, and an elevated change in the band gap after gas adsorption. [33][34][35] In the experimental study, Gui et al fabricated a sensor based on a Ni-modified carbon nanotube, which can detect SF 6 decomposition components at a concentration of 1 ppm. 36 Ivanov et al reported that the change in the resistance of Pt-doped SnO 2based sensors was 2 to 55 times higher than that of commercial sensors.…”
Section: Introductionmentioning
confidence: 99%
“…To pick the stable Pt-doped HfS 2 for adsorbing gas dissolved in insulating oil, the calculation of doping energy ( E d ) is necessary. According to the previous report, E d could be obtained by the following formula E d = E normalP normalt normalH normalf S 2 E normalP normalt E normalH normalf S 2 where E Pt‑HfS 2 , E Pt , and E HfS 2 are the energy of the doping structure, Pt dopant, and HfS 2 monolayer, respectively. E d is the interaction force that exists between the dopant atoms and the semiconductor.…”
Section: Calculationmentioning
confidence: 99%